Gramsci 's contribution to research on the education project of the bourgeois class in Brazil (PerCursos, 2024)
This article, bound to a project funded by the Research Support Foundation of Minas Gerais, addresses the theoretical-methodological contribution of Antonio Gramsci to the research on the project of the bourgeois class for public education. In this sense, the article i) highlights the author's contribution to knowledge production and its purpose; ii) points out the central concepts for the analysis of the mentioned object; iii) presents examples of the performance of the bourgeoisie to order the schooling of the working class. Emphasizing that education needs to be addressed concerning hegemony, the article alludes that the topicality of Gramsci's thought also lies in the definition of elements for the construction of the anti-capitalist project of education committed to human emancipation.
Keywords: Gramsci; public education; bourgeois class